What can we learn from Tamás Varga’s work regarding the arithmetic-algebra transition? - Szanyi, Gyöngyi; Jánvári, Zsuzsanna (Teaching Mathematics and Computer Science, 2020)
Tamás Varga’s Complex Mathematics Education program plays an important role in Hungarian mathematics education. In this program, attention is given to the continuous “movement” between concrete and abstract levels. In the process of transition from arithmetic to algebra, the learner moves from a concrete level to a more abstract level. In our research, we aim to track the transition process from arithmetic to algebra by studying the 5-8-grader textbooks and teacher manuals edited under Tamás Varga’s supervision. For this, we use the appearance of “working backward” and “use an equation” heuristic strategies in the examined textbooks and manuals, which play a central role in the mentioned process. Subject Classification: 97-01, 97-03, 97D50